DOWNLOADING THE POETIC SELF : an anatomy of poetic character. - WILL, FREDERIC ([Place of publication not identified] : CAMBRIDGE SCHOLARS PUBLIS, 2018)
This volume presents an autobiography of one writer's existence in poetry, the tracks left by a clumsy bear taming himself in public; it is also a forum in which to act out and discover oneself. It will serve to light fires, the can-do drive others can surpass, finding in themselves language as daring as their lives, and more daring than the author's. It endeavours to allow every reader of this text to leave it feeling better, more able to do things by him- or herself, and more convinced that poetry is essential to a good life. The text itself is the eighth title in the 10-volume series Inside.
Intro -- Table of Contents -- Introduction -- Part One: Poems of Intervention -- Chapter One -- Chapter Two -- Chapter Three -- Chapter Four -- Chapter Five -- Chapter Six -- Chapter Seven -- Part Two: Modifying Intervention -- Chapter Eight -- Chapter Nine -- Chapter Ten -- Part Three: Serene Years -- Chapter Eleven -- Part Four: Arguments with Charon -- Chapter Twelve -- Part Five: Gosh, after all That? -- Chapter Thirteen -- Postlude -- Chapter Fourteen -- Poem Texts and Translations -- Index.
Includes index.
Print version record.
eBooks on EBSCOhost
Keywords: Will, Frederic -- Criticism and interpretation; Will, Frederic; Poetry -- History and criticism; Poésie -- Histoire et critique; Literary studies: general; Literary studies: poetry & poets; Philosophy: aesthetics; LITERARY CRITICISM -- Poetry; Poetry; Criticism, interpretation, etc